(untitled) (Revista de Ciências Agroveterinárias, 2006)
In the search for approval by the in force science and proceeding from the Cartesian model, the medicinal plants are decomposed in molecules, and sometimes, the main purpose of the therapeutic action, so important in the conception of integral health, is lost. This paper ames to discuss the contribution of systems such as: the Chinese and the Indian medicine, the Anthroposophic and the one of the indigenous communities which contemplate a wider coverage in the concept of health, and may help in the use of medicinal plants for humanity’s welfare.